Weather Extremes in the Mediterranean Winter Are Associated With Reduced Apparent Survival and Delayed Initiation of Egg‐Laying in a Migratory Raptor - Kujala Inga; Nebel Carina; Pöysä Hannu; Korpimäki Erkki (Wiley-Blackwell, 2026)
Climate change increases the occurrence of extreme weather conditions, affecting ecosystems worldwide but possible impacts of these extremes on biological systems have been insufficiently studied. Among others, migratory raptors are particularly susceptible to adverse weather conditions. We analysed capture-recapture data of Eurasian Kestrels (Falco tinnunculus) breeding in western Finland during 1985–2018 to study how environmental conditions in their boreal breeding areas and Mediterranean wintering areas affect adult survival rate. As predictors of apparent survival, we used density data of their primary prey (voles) from their breeding grounds, alongside seasonal minimum temperatures and rainy-day frequencies of Finnish summer and Mediterranean winter. We also tested whether adverse weather in winter can result in carry-over delays in the initiation of next breeding season (i.e., egg-laying). We found that both frequent and infrequent rain in winter predicted low apparent survival rate, while summer weather conditions had no effect on survival. Vole abundance in breeding areas negatively correlated with apparent survival. Finally, frequent precipitation in Mediterranean wintering grounds resulted in delayed laying in the following spring during years of low vole abundance in the breeding grounds. We conclude that weather extremes in wintering areas are more acutely affecting annual adult survival in long-distance migratory kestrels than weather conditions in breeding grounds, thus providing the first evidence of impacts of climate extremes on survival rate of migratory species in North Europe. Furthermore, our results suggest that effects of such disadvantageous weather conditions carry over from winter to spring. If climate change amplifies the frequency and magnitude of weather extremes in the Mediterranean, its long-distance migrant inhabitants may encounter setbacks in population growth and stability.